Hawksbill turtles visit moustached barbers: cleaning symbiosis between eretmochelys imbricata and the shrimp stenopus hispidus - Sazima, Ivan (2004)
This seems to be the first record of cleaning symbiosis between marine turtles and shrimps. During their foraging on the reef flat, the turtles regularly visited and posed at the stations. The same stations were visited by a few species of reef fishes, which posed and were cleaned by the shrimps. We suggest that cleaning symbiosis between turtles and shrimps is widespread and went unrecognised due to the superficial resemblance between a resting turtle and a posing and cleaned one. Additionally, we submit a putative origin for the cleaning symbiosis between marine turtles and cleaner shrimps following a few simple behavioural steps.